Change Management in the Implementation of Teachers' Code of Ethics - Weni Ayu Sunita Zandroto; Yuniarto Mudjisusatyo; Arif Rahman; Syawal Gultom; Eka Daryanto; Aman Simare-mare; Rosnelli Rosnelli; Sukarman Purba (Journal of The Community Development in Asia, 2025)
This study examines the implementation of change management concerning the teacher code of ethics at SMA Unggul Del in the context of Generation Z student behavior. The objective is to evaluate the extent and effectiveness of change management strategies applied to the teacher's code of ethics in addressing the specific behavioral characteristics of Generation Z students within this educational setting. Employing a qualitative case study approach, data were collected through interviews with teachers and students, classroom observations, and questionnaires to gain comprehensive insights. The findings revealed inconsistencies between teachers' comprehension of the ethical code and its practical application, alongside difficulties in managing technology use, a prominent aspect of Generation Z's behavior. Consequently, this research suggests the necessity of targeted change interventions, such as continuous professional development and collaborative strategy development. In conclusion, effective change management is crucial for enhancing the practical application of the teacher code of ethics, thereby fostering a more supportive and productive learning environment tailored to the needs of Generation Z students